Student Delinquency at Prestigious Schools - Agung Tri Prasetia; Ade Putra Hayat; Rhomiy Handican; Yan Guspriadi; Syukron Saputra; Agung Tri Prasetia; Ade Putra Hayat; Rhomiy Handican; Yan Guspriadi (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2026)
This study examines the phenomenon of student delinquency within elite boarding schools, challenging the dominant assumption that prestigious educational institutions inherently guarantee holistic student development. Using a qualitative exploratory case study design, research was conducted in three upper-class boarding schools in Indonesia. Data were collected over a three-month period through in-depth interviews, field observations, and document analysis, involving 29 participants consisting of students, teachers, dormitory supervisors, counselors, and parents. Thematic analysis was employed to identify recurring patterns and underlying meanings in participants’ lived experiences. The findings reveal four interconnected themes: symbolic pressure within dormitory environments, student resistance to institutional rules, cold and functional patterns of parental communication, and delinquency as a form of identity expression. Symbolic competition related to lifestyle, family background, and social status shapes peer interactions and generates psychosocial strain. Institutional discipline, while designed to foster excellence, may unintentionally restrict identity exploration, leading students to express autonomy through rule-breaking behaviors. Furthermore, achievement-oriented and emotionally distant parenting patterns contribute to feelings of alienation and limited affective support. The study integrates sociological, psychological, and Islamic educational perspectives to interpret delinquency as a relational and structural response rather than mere deviance. The findings suggest that elite educational settings require a balanced approach that integrates academic rigor, moral cultivation, and emotional well-being. This research contributes to broader discussions on educational quality by highlighting the need to reconsider how prestige, discipline, and family expectations shape adolescent development in competitive schooling environments.